Unusual Punishment: The Federal Death Penalty in the United States - John Brigham (Washington University Journal of Law & Policy, 2004)
This material has been presented at Southern Cross University, the Law and Society meetings in Budapest, the University of Georgia, Victoria University, Melbourne University, and LaTrobe University in Australia. The Essay examines the way state and federal legal authority is constituted in the United States by focusing on local jurisdictions that do not have capital punishment as they respond to the federal death penalty. Particular attention is given to both the prosecution of Kristen Gilbert, a nurse who was tried for capital murder in Massachusetts, and research on the federal courts in Puerto Rico.
Keywords: Capital punishment; Federal government